DESAIN MONETARY POLICY RULE UNTUK PEREKONOMIAN TERBUKA: KASUS INDONESIA - Budhiasa, G. Sudjana (IQTISHODUNA, 2012)
This paper is trying developing a small scale Keynesian macroeconometric model for Indonesia as the main framework to explain some characterized of macroeconomic variables and its transmission path in order to understand how economy of one country is work. However, the main goal of the developing this macroeconomic model is based on monetary perspective, so that the model would be linked with policy framework of Central Bank as guidance and its strategy for combating inflation and at the same time can be achieve the expansion of employment and economic growth as well. This macroeconometric model is transmitted facilities and take function as the macroeconomic channel for testing the effectively of BI rate as monetary instrument. So that the model as developed in this paper will be examine using 2SLS simultaneous econometricÂ  methods and the next simulation process as an effort in understanding the fenomena as Indonesian economy is working under the recognition ofÂ  monetary instrument policy.